Smartwatch Potentials for Healtcare - Yahdi Siradj (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
As a member of wearable devices family, the smartwatch is having big potentials to contribute improving the healthcare and wellness of human being. At this time, smartwatch has been supported by varies sensor chips which are unthinkable for recent decades that can be fitted into small devices as small as a wristwatch. Such sensors as accelerometer, gyro meter, motion tracking, temperature, humidity etc. Integrating those sensors with big data technology, together with Artificial Intelligence will leverage smartwatch’s impact into another higher level, especially in healthcare and wellness domain. At least, the future of smartwatch will be fully contributing around Continuous monitoring enables prevention, Therapy, Tools for specific patient groups, Electronic patient records. With continuous improving sensor technology and more sensor will be produced in the future, smartwatch is giving high opportunity to revolutionize the way human being undergo healthy life in the day after tomorrow.